2022
DOI: 10.1186/s13017-022-00454-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of viscoelastic hemostatic assay to guide hemostatic resuscitation in trauma patients: a systematic review

Abstract: Objective Viscoelastic hemostatic assay (VHA) provides a graphical representation of a clot’s lifespan and reflects the real time of coagulation. It has been used to guide trauma resuscitation; however, evidence of the effectiveness of VHAs is still limited. This systematic review aims to summarize the published evidence to evaluate the VHA-guided strategy in resuscitating trauma patients. Methods The PubMed, Embase, and Web of Science databases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Our analysis also demonstrated that the total cost of blood product transfusions in the thromboelastography-guided transfusion group was significantly lower than in the conventional transfusion group as a result of transfusion avoidance. Although there are conflicting data regarding the cost-effectiveness of thromboelastography across different systematic analyses in various patient populations, such as those with trauma-induced coagulopathy and those undergoing liver and cardiac surgery (37)(38)(39), one study showed that, in patients undergoing liver transplantation, a thromboelastography-based hemostatic management approach compared with the standard of care, lead to significant cost savings associated not only with transfusion avoidance but also with length of ICU stay and reoperation for bleeding (40).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also demonstrated that the total cost of blood product transfusions in the thromboelastography-guided transfusion group was significantly lower than in the conventional transfusion group as a result of transfusion avoidance. Although there are conflicting data regarding the cost-effectiveness of thromboelastography across different systematic analyses in various patient populations, such as those with trauma-induced coagulopathy and those undergoing liver and cardiac surgery (37)(38)(39), one study showed that, in patients undergoing liver transplantation, a thromboelastography-based hemostatic management approach compared with the standard of care, lead to significant cost savings associated not only with transfusion avoidance but also with length of ICU stay and reoperation for bleeding (40).…”
Section: Discussionmentioning
confidence: 99%
“…Many, although not all, studies have demonstrated that treatment algorithms based on VET resulted in reduced transfusion requirements in TIC [20,29,[81][82][83][84][85][86]. Two studies in trauma patients that compared transfusion requirements before and after implementation of a TEG-guided resuscitation protocol reported significantly lower RBCs and FFP transfusion rates [82,83].…”
Section: The Effect Of Viscoelastic Test On Allogenic Blood Transfusionmentioning
confidence: 99%
“…Since there is no score to assess complete coagulation chain and predict massive transfusion in trauma management, Viscoelastic hemostatic assays (VHA) have been proposed for many years to provide personalized management of TIC 49 . ThromboElastoGraphy and ROTational thromboElastoMetry use (TEG/ROTEM) reduces the total amount of blood product transfused, with more fibrinogen and plasma replacement 50 . Viscoelastic hemostatic assays are progressively becoming standard of care for the early diagnosis of TIC, including for coagulation activation evaluation, clot strength and fibrinolysis 51 .…”
Section: Trauma-induced Coagulopathymentioning
confidence: 99%
“…49 ThromboElastoGraphy and ROTational thromboElastoMetry use (TEG/ROTEM) reduces the total amount of blood product transfused, with more fibrinogen and plasma replacement. 50 Viscoelastic hemostatic assays are progressively becoming standard of care for the early diagnosis of TIC, including for coagulation activation evaluation, clot strength and fibrinolysis. 51 Recent studies are including VHAs to guide therapy after initial WB administration (STORHM trial-NCT04431999, SWAT trial-NCT 03402035).…”
Section: Trauma-induced Coagulopathy Viscoelastic Hemostatic Assaymentioning
confidence: 99%